Implementation of Good Governance in Health Services at the UPTD Mental Hospital of the Bangka Belitung Islands Province - Fikri, Zakiyudin; Asmadi, Asmadi; Sari, Dara Puspita (Jurnal Ilmu Administrasi Negara (JUAN), 2024)
This research discusses the implementation of good governance in health services at the UPTD Regional Mental Hospital, Health Service of the Bangka Belitung Islands province. With indicators of the principle of public accountability, the principle of legal certainty and the principle of public transparency. This research aims to find out how Good Governance is implemented in Health services at the UPTD Regional Mental Hospital, Health Service of the province of Bangka Belitung Islands and the factors that influence the Implementation of Health Services. This research is qualitative research with descriptive methods carried out by the UPTD of the Regional Mental Hospital of the Bangka Belitung Islands Provincial Health Service. The results of this research show that the implementation of Good Governance in Health services at the UPTD Regional Mental Hospital, Health Service of the Bangka Belitung Islands province is quite good but not yet optimal, especially the timeliness of services seen from the principle of public accountability, from the principle of legal certainty it is quite good but not yet optimal because there are still discrimination in services provided and the principle of public transparency is seen to be quite good. This is influenced by several factors, including: Moral and ethical principles of hospital employees, the absence of hospital regulations that regulate legal guarantees for patients and employees and there is still miscommunication between hospital employees and patients regarding the flow of health services